2013
DOI: 10.1186/1471-2458-13-716
|View full text |Cite
|
Sign up to set email alerts
|

Rank, job stress, psychological distress and physical activity among military personnel

Abstract: BackgroundPhysical fitness is one of the most important qualities in armed forces personnel. However, little is known about the association between the military environment and the occupational and leisure-time dimensions of the physical activity practiced there. This study assessed the association of rank, job stress and psychological distress with physical activity levels (overall and by dimensions).MethodsThis a cross-sectional study among 506 military service personnel of the Brazilian Army examined the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
5
28
4
4
Order By: Relevance
“…This fear was also found in the U.K., Canadian, Australian and New Zealand Defence Forces [244]. Research on the Brazilian army found that those who suffer from psychological distress also have a high prevalence of leisure time physical inactivity [63]. This type of inactivity may lead to several physical medical problems, such as obesity, which can, in turn, affect individual’s occupational ability.…”
Section: Psychological Impactmentioning
confidence: 92%
See 2 more Smart Citations
“…This fear was also found in the U.K., Canadian, Australian and New Zealand Defence Forces [244]. Research on the Brazilian army found that those who suffer from psychological distress also have a high prevalence of leisure time physical inactivity [63]. This type of inactivity may lead to several physical medical problems, such as obesity, which can, in turn, affect individual’s occupational ability.…”
Section: Psychological Impactmentioning
confidence: 92%
“…A study on the Brazilian military found that higher levels of job stress were associated with high levels of occupational physical activity, but not high levels of leisure time activity [63, 64]. These studies indicate that the benefits of physical activity occur as a result of participating in leisure time activity and not occupational physical activity.…”
Section: Physical Fitnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Observaram que os animais com alta capacidade ao exercício de resistência exibiram maior comportamento de ansiedade do que os animais com baixa capacidade para o exercício, e ainda exibiram maiores níveis de corticosterona [33]. Contudo, Martins e Lopes [34], avaliando militares brasileiros, observaram associação do estresse devido ao trabalho e do sofrimento psicológico (identificado por sintomas de depressão e nervosismo) com baixos níveis de atividade física na prática de esportes/exercícios.…”
Section: Artigo Originalunclassified
“…(Owen et al, 2010;Sitthipornvorakul et al, 2014). In addition to this, intense usage of new technological advances and applications, and increasing demands (Lopes et al, 2010) might cause an increase in the prevalence of chronic disease, stress, and psychological problems (Dunstan et al, 2012;Martins and Lopes, 2013). 1.4 billion adults all over the world are reported to be inactive (WHO, 2018).…”
Section: Introductionmentioning
confidence: 99%